Situational Violence of the Couple: Comparing Quantitatively Hypothesis Derived from de the Gender and the Familiar Violence Perspectives [Violencia Situacional de Pareja: Contrastando Cuantitativamente Hipótesis Derivadas de la Perspectiva de Género y de la Perspectiva de Violencia Familiar] - Fernandez-Tapia, A (Fundacion Aigle, 2019)
Intimate partner violence is considered a public health problem. The Social Sciences have attempted to explain this behavior mainly from the Theory of Gender and Theory of Family Violence. The present study analyzes, in 112 couples, the relationship between general and specific aggression, and the distribution of specific aggression within the couples in order to test the hypothesis of both theoretical frameworks. The results show a positive correlation between levels of general and specific aggression in the couple. Also, we find that physical aggression and coercive control are asymmetrically distributed within dyads being women higher in the expression of these behaviors. Results are discussed contrasting both theories. © 2019 Fundación AIGLÉ.
Keywords: Coercive control; Domestic violence; Gender violence; General aggression; Situational partner violence